A marcha das margaridas: lutas sociais e resistências das mulheres trabalhadoras rurais no Brasil no século XXI - SILVA, Berenice Gomes da (2021)
This thesis has as its object of study the March of Margaridas, a strategy for mobilizing rural women workers that configures itself as an expression of social struggle and brings together various feminist and rural and urban women's movements. The self- organization of rural women workers emerged in Brazil, in the 1980s, in the context of struggles of social and popular movements, particularly in rural unionism and influenced by the feminist movement and sectors of the progressive Catholic Church. The March of Margaridas resulted from this process and emerged, in 2000, influenced by international feminist struggles against neoliberalism to counteract the situation of poverty and exploitation of women and also the reorganization of urban unionism. The objective of the research is to analyze the March of Margaridas, as an expression of social struggles carried out by rural women workers, in order to understand how it reconfigures itself from a “specific” mobilization to a broader perspective of a class, popular and feminist character. To investigate this process, I analyzed how this March was constituted in organizations and movements of rural women workers and its relationship with the trade union movement and the feminist movement, and also how the process of generating and using information, of popular communication, that together with the construction of the agenda and political formation are used as strategies in this March as they are part of its political and ideological project. The empirical analysis took place during the Marcha das Margaridas 2019, in its local organization, in Maranhão, and also in its realization in Brasília (DF). Analyzes indicate that this March expanded its strategy of gaining visibility and demanding "specific" programs for women for a broad mobilization in defense of democracy against labor and social security reforms, in addition to proposing a new model of society that opposes the capitalism in its most predatory phase, represented by ultraliberalism. To this expansion I attribute the insertion of broad sectors of social, popular and feminist movements, as well as the expansion and radicalization of the agenda that became even a political platform and the Brazilian situation after the 2016 coup that deepened the neoliberal agenda, removed rights and revealed the contradictory character of the Brazilian state and society.